Nomadismo digital e os discursos construídos no território informacional: uma análise dos blogs 360meridianos e Nômades Digitais - Barroso, Letícia Gomes (2021)
The Digital Nomadism is a movement formed by two actions that are usually considered as distinct, traveling and working, however, with the emergence of this movement, they started to be seen as conected activities. This study, therefore, aims to understand this lifestyle through the analysis of two weblogs in Brazil, Nômades Digitais and 360meridianos. With this analysis, we intend to identify the discoursive elements that build this movement narrative. The analysis intends to identify either the emergency of the movement and also the figures, themes and values transmited by the agents. Besides, we aim to understand how they, the Digital Nomads, explain the new setting of liberal labour. In order to form the corpus of the research, we chose three posts, one from Nômades Digitais and another from 360meridianos. On Nômades Digitais, due to the lack of updates, we chose only on post, “Manifesto Nômade”, aiming to understand the emergence of the movement in Brazil. On 360meridianos, two posts have been selected, one before the COVID-19 pandemic and another during it, with the interest of seeing the change on the subjects of the posts, incluing the change of the discourse. We based our analysis on the Discoursive Semiotics, seen by Greimas (2016), Barros (2005) and Fiorin (2002, 2016). Futhermore, on this research we have identified, elements such as semiotic themes and figuresm and the categorizing that can manipulate the subject to get this lifestyle. About the narrativities of entrepeneurship, we used the thoughts of Casaqui (2016, 2018 e 2020), and connected to it, the inspirational ways seen. Rudiger (2010), on the same way, helped us understand the Self-help literature characteristics and how the discourse of digital nomadism can be built from the neoliberal perspective. On the neoliberal individual and the new spirit of capitalism, we resorted to Dardot e Laval (2016) and Boltanski e Chiapelo (2009), in order to comprehend how Digital Nomadism is related to the neoliberal principles, since it is more than the movement of traveling and working, it is something that can change the way how the labour rights work, especially in Brazil.